Does wobble board training improve balance in older adults? A systematic review. (22nd October 2021) - ALJawaee, Madawi A.; Jones, Michael D.; Theobald, Peter S.; Williams, Jonathan M.
Abstract: Background: Falls are a common and costly problem, with poor balance a significant contributor. Wobble boards are commonly used for balance enhancement. However, the efficacy of wobble board training is not well understood, particularly in the older adult. Objectives: To appraise and synthesise literature pertaining to the effect of wobble board training on balance in older adults. Methods: A systematic search of Medline, Scopus, EBSCO, CINAHL, Science Direct, and Google Scholar databases was conducted up to August 2020. Articles comparing balance before and after wobble board training were included and quality appraised using the modified Downs and Black checklist. Results: Six relevant studies ( n  = 129) were identified for review: four randomised-controlled-trials, one pilot-study and one repeated-measures design. The overall weighted average percentages, calculated from those studies where possible suggested an improvement in Berg Balance Scale (or similar) was 4.4% and for timed-up and go, 6.3%. Mean effect sizes ranged from 0.09 to 0.96. Overall, there is conflicting evidence to support wobble training for balance improvement in older adults. Magnitude of real change was often small questioning the impact of such small improvements on overall balance function. Effect sizes for balance enhancement through wobble board training were modest, with the largest effects on multi-modal balance outcome measures, such as the Berg Balance Scale. The results indicate that if wobble board programmes are simple and of a sufficient 'within session' duration, then some improvements in balance can be demonstrated within 3-weeks. Conclusions: The evidence suggests conflicting results for the improvement of balance with wobble board training in older adults. Where effects were seen their magnitude was modest. Future studies should focus on determining the optimal wobble board programme to enhance balance.